2001
DOI: 10.2307/2695108
|View full text |Cite
|
Sign up to set email alerts
|

Properties of ideals on the generalized Cantor spaces

Abstract: Abstract. We define a class of productive σ−ideals of subsets of the Cantor space 2 ω and observe that both σ −ideals of meagre sets and of null sets are in this class. From every productive σ −ideal J we produce a σ −ideal J κ of subsets of the generalized Cantor space 2 κ . In particular, starting from meagre sets and null sets in 2 ω we obtain meagre sets and null sets in 2 κ , respectively. Then we investigate additivity, covering number, uniformity and cofinality of J κ . For example, we show thatOur resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…We investigate relations between transitive cardinal coefficients of J and those of J κ . Some of them are similar to relations between standard cardinal coefficients of J and J κ proved in [5]. We omit the proofs, as they are also analogous.…”
Section: Transitive Cardinal Coefficients Of Ideals On 2 κmentioning
confidence: 80%
See 3 more Smart Citations
“…We investigate relations between transitive cardinal coefficients of J and those of J κ . Some of them are similar to relations between standard cardinal coefficients of J and J κ proved in [5]. We omit the proofs, as they are also analogous.…”
Section: Transitive Cardinal Coefficients Of Ideals On 2 κmentioning
confidence: 80%
“…In particular, starting from meagre sets and null sets in 2 ω we obtain meagre sets and null sets in 2 κ , respectively. This description gives us a powerful tool for investigating combinatorial properties of ideals on 2 κ , which was done in [5]. In this paper we continue our research, focusing on transitive cardinal coefficients of ideals of subsets of 2 κ .…”
Section: Introduction Definitions and Basic Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2001 Kraszewski in [4] defined a class of productive σ-ideals of subsets of the Cantor space 2 ω and observed that both σ-ideals of meagre sets M and of null sets N are in this class. Next, from every productive σ-ideal J one can produce a σ-ideal J κ of subsets of the generalized Cantor space 2 κ .…”
Section: Introductionmentioning
confidence: 99%